Resilience of Adolescents Experienced with Broken Home - Dewi Angreini; Andi Tadjuddin; Herman (IJESS International Journal of Education and Social Science, 2024)
This research explores resilience from family dysfunction in teenagers who experience broken homes by selecting as subjects children from SMA 5 Makassar. The focus of this research is the relationship between broken home family dysfunction, changes in adolescent attitudes and resilience. The method used in this research is a qualitative research method using observation and interview techniques to better understand the dysfunctional situation of broken home families experienced by teenagers at SMA 5 Makassar. The subjects of this research were two people, namely a woman and a man, both of whom were students at SMA 5 Makassar. Both subjects are in the same situation, namely that their parents are divorced. The lack of love from both parents makes him tend to do various negative things as a resilience mechanism for himself. This research also aims to determine the description of the resilience of teenagers who have broken homes at SMA 5 Makassar. It is hoped that the results of this research can provide a significant contribution in developing more effective intervention approaches among teenagers, especially those experiencing broken homes.